2021
DOI: 10.51585/gjvr.2021.2.0012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the efficacy of three inactivated H9N2 influenza vaccines on broiler flocks

Abstract: This study was carried out to evaluate the effect of different Low Pathogenic Avian Influenza (LPAI) H9N2 vaccines containing different virus strains (vaccine A, vaccine B, and vaccine C) on the productivity and immunity of 10 days-old broiler chickens. Two hundred day-old Cobb broiler chicks were divided into eight groups, 25 chicks in each group. Six groups were vaccinated with Vaccine A, Vaccine B, and Vaccine C (2 groups/each vaccine) at 10 day-old, respectively. Chickens of groups 7 and 8 were kept as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The significant variation of WG between groups may occur due to the effect of different types of vaccines used. These results agreed with Essalah-Bennani et al (28) when they showed significant differences in the vaccination with three types of AI-H9N2 inactivated vaccines; thus, the explanation of high values in WG at 28 and 35 days may be due to the limited number of chicks in each group, high quality of feed and standard condition of rearing. Our results represent the actual data of the experiment and are close to the standard parameters of WG in the ROSS308 broilers guide.…”
Section: Discussionsupporting
confidence: 91%
“…The significant variation of WG between groups may occur due to the effect of different types of vaccines used. These results agreed with Essalah-Bennani et al (28) when they showed significant differences in the vaccination with three types of AI-H9N2 inactivated vaccines; thus, the explanation of high values in WG at 28 and 35 days may be due to the limited number of chicks in each group, high quality of feed and standard condition of rearing. Our results represent the actual data of the experiment and are close to the standard parameters of WG in the ROSS308 broilers guide.…”
Section: Discussionsupporting
confidence: 91%
“…LPAI has a global distribution with regional variations in type and the targets of infection. The H9N2 subtype is an example of a LPAI pathotype affecting poultry worldwide, and is endemic to Asia, the Middle East and Africa [39][40][41]. Another LPAI, H7N9 was identified as the cause of several outbreaks in China but has not been isolated in other parts of the world.…”
Section: Avian Influenza Virus (Aiv)mentioning
confidence: 99%
“…According to experimental research, the closer the vaccine is to the field strain, the less virus is released in exposed birds. 37 Genetic variation is a significant issue with avian influenza vaccines, as it reduces immunization effectiveness. Antigenic drift is considered to unfold when the field virus changes in response to the host's antibodies.…”
Section: The Emergence and Evolution Of The Lpai H9n2 Virus A Brief H...mentioning
confidence: 99%
“…34 Oil-based inactivated H9N2 LPAI vaccines were used in the poultry sector in many countries to avoid H9N2 infection owing to the extensive essence of H9N2 viruses and their zoonotic potential. 7,[35][36][37] However, because the nature of HA antigenic epitopes is constantly changing, influenza vaccines must be updated each year to make sure strain-specific immunity, posing a significantly challenging task to vaccine manufacturers. As a result, a global flu vaccine with broad protection against conserved influenza protein regions is required.…”
Section: Introductionmentioning
confidence: 99%